The possibilities of using the inhibitors of matrix metalloproteinases for keratoplasty - K. V. Sirotkina; E. V. Chentsova (Трансплантология (Москва))
Introduction. The review is devoted to the actual problem of treating patients with keratolysis. The role of matrix metalloproteinases in the pathogenesis of cornea and corneal graft melting is discussed as well as the practical experience of using synthetic metalloproteinase inhibitors in various branches of medicine and in ophthalmology, in particular. In the field of eye diseases, the search for effective methods for the treatment of corneal injuries of various origins, as well as its post-transplant complications, has been underway for a long time. Recent studies have shown that local imbalance of matrix metalloproteinases and their inhibitors system, as well as the immune system status, may play the main role in the outcome of urgent keratoplasty, and the use of synthetic metalloproteinase inhibitors can significantly improve the biological result of the donor cornea transplant. The role of platelets in the regulation of the proteolytic system has not been fully studied. However, some literature data on the platelet-associated inhibitor of metalloproteinases and the use of platelet-rich plasma to correct the collagenolytic activity of enzymes are of great interest to ophthalmologists, due to therapeutic efficacy and simple method of producing its production the autologous platelet-rich plasma.The present brief literature review covers the pathogenesis and clinical features of keratolysis, factors which can affect the outcome of urgent keratoplasty, describes the features of matrix metalloproteinases, their inhibitors, and the plateletrich plasma as a potential endogenous source of a tissue inhibitor of matrix metalloproteinases.Aim. To evaluate the possibility of using inhibitors of matrix metalloproteinases for keratoplasty based on a literature review.Material and methods. To write the review article, we have made the search in the homeland eLibrary.RU database and in the PubMed resource database to select the articles on the topic published in the period from 1985 to 2022.